2023
DOI: 10.3390/toxics11070583
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk and Quality Assessment of Vegetables Cultivated on Soils from a Heavily Polluted Old Mining Area

Abstract: Three garden vegetables—radish, carrot and lettuce—were cultivated in a pot experiment using two soils from the Příbram area polluted mainly by cadmium (Cd), zinc (Zn), lead (Pb) and chromium (Cr). The soils of the Příbram district, Czech Republic, are heavily polluted as a result of the atmospheric deposition of toxic elements originating from historic lead–silver mining and smelting activities. The results showed that lettuce absorbed the highest amounts of toxic elements (Cd 28 and 30, Cr 12 and 13, Zn 92 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…According to Zhu et al [61], N metabolism is central to the plant response to TEs, and its influence by TEs is related to the changes in free AA metabolism. Even though changes in AA metabolism in plants can vary widely due to the influence of TEs and the plant itself, several researchers have confirmed that AA increases in plant leaves and roots are caused by As, Cd, Pb, and Zn [3,[61][62][63][64][65][66][67][68]. Consistent with these results, the TEs of the multicontamination group induced an increase in total free AA content in lettuce leaves, while the content in the lettuce roots was not significantly affected.…”
Section: Impact Of Toxic Element Multicontamination On the Metabolic ...mentioning
confidence: 65%
See 2 more Smart Citations
“…According to Zhu et al [61], N metabolism is central to the plant response to TEs, and its influence by TEs is related to the changes in free AA metabolism. Even though changes in AA metabolism in plants can vary widely due to the influence of TEs and the plant itself, several researchers have confirmed that AA increases in plant leaves and roots are caused by As, Cd, Pb, and Zn [3,[61][62][63][64][65][66][67][68]. Consistent with these results, the TEs of the multicontamination group induced an increase in total free AA content in lettuce leaves, while the content in the lettuce roots was not significantly affected.…”
Section: Impact Of Toxic Element Multicontamination On the Metabolic ...mentioning
confidence: 65%
“…Floodplain soils of the Litavka River (Příbram region, Czech Republic) are heavily multicontaminated by historic lead-silver mining and smelting activities and extreme flooding events that occurred at various time between 1932 and 2002 [1]. Analyses from this region have shown that the highest enrichment levels of soils are observed for Pb, Zn, Cd, and As [2,3]. The effect of soil multicontamination on plants is influenced by many factors, such as availability, mobility, and oxidation state of TEs in soil; interactions between elements; soil properties (pH, redox potential, texture, clay content, and soil organic matter); plant species and cultivars; and plant growth period [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a decline in the total content of free AAs was observed in the roots, but this was not a statistically significant difference between the variants (Table 3). Similarly, the decrease in free AA content was confirmed in edible parts of carrot, radish and lettuce growing on strong multi-contaminated soil [86]. Zhu et al [87] observed a significant decrease in AAs in the roots of Crassocephalum crepidioides caused by Cd applied to soil.…”
Section: Response Of Free Amino Acids To CD Pb and Znmentioning
confidence: 78%
“…The Cd, Pb and Zn content was determined according to Pavlíková et al [86]. Briefly, homogenised dry material (0.5 ± 0.05 g) was digested in 10 mL of a mixture of HNO 3 and H 2 O 2 (4:1, v/v) in an Ethos 1 device (MLS GmbH, Leutkirch im Allgäu, Germany).…”
Section: Determination Of Toxic Elementsmentioning
confidence: 99%